Computed Tomography-Guided Methylene Blue Localization: Single vs. Multiple Lung Nodules - Lin, Chia-Ying; Chang, Chao-Chun; Huang, Li-Ting; Chung, Ta-Jung; Liu, Yi-Sheng; Yen, Yi-Ting; Tseng, Yau-Lin (Frontiers in Medicine, 2021)
Background: Preoperative localization for small invisible and impalpable pulmonary nodules is important in uniportal video-assisted thoracoscopic surgery (VATS). Localization of multiple ipsilateral pulmonary nodules during VATS resection remains challenging. The aim of our study is to elucidate the efficacy of preoperative CT-guided methylene blue localization of both single and multiple pulmonary nodules. Methods: Consecutive patients undergoing preoperative CT-guided methylene blue dye localization for lung nodules, followed by VATS resection, were retrospectively analyzed between January 2014 and November 2019. Chi-square tests, Fisher's exact test and independent T-test were used to compare variables between the groups. Logistic regression was used to identify risk factors for procedure-related complications. Results: A total of 388 patients, including 337 with single nodule and 51 with multiple nodules, were analyzed. The success rate of preoperative CT-guided methylene blue localization for both single and multiple pulmonary nodules were comparable as 98.8% (333/337) versus 100% (108/108). The procedure time was longer (23.2 ± 9.4 versus 7.6 ± 4.8 minutes, p <.001) and risk of pneumothorax was higher (47.1% versus 25.5%, p = .002) in multiple nodule group. Age (odds ratio [OR] 1.027; 95% CI= 1.004 - 1.050; p = .021) and procedure time (OR 1.087; 95% CI= 1.043 - 1.132; p <.001) were independent risk factors for pneumothorax. Nodule depth (OR 2.829; 95% CI= 1.259 - 6.356; p = .011) was an independent risk factor for pulmonary hemorrhage. Conclusions: Preoperative CT-guided methylene blue localization for both single and multiple pulmonary nodules is safe, feasible and effective.